Taming the wild field : colonization and empire on the Russian steppe - Sunderland, Willard, 1965- (Cornell University Press ; University Presses Marketing [distributor], 2006)
"Traversing a thousand years of the region's history, Willard Sunderland recounts the complex process of Russian expansion and colonization, stressing the way outsider settlement at once created the steppe as a region of empire and was itself constantly changing. The story is populated by an array of administrators, Cossack adventurers, Orthodox missionaries, geographers, foreign entrepreneurs, peasants, and (by the late nineteenth century) tourists and conservationists. Sunderland's approach to history is comparative throughout, and his comparisons of the steppe with the North American case are especially telling.